2012
DOI: 10.1002/jocb.12
|View full text |Cite
|
Sign up to set email alerts
|

One Size Does Not Fit All: Managing Radical and Incremental Creativity

Abstract: This research extends creativity theory by re-conceptualizing creativity as a twodimensional construct (radical and incremental) and examining the differential effects of intrinsic motivation, extrinsic rewards, and supportive supervision on perceptions of creativity. We hypothesize and find two distinct types of creativity that are associated with different motivational factors. We further consider how combinations of motivational factors are linked to the different types of creativity. Finally, theoretical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 75 publications
3
71
0
3
Order By: Relevance
“…Also, employees' perceptions of creativity could more accurately reflect creative habits as some employees may shield such behavior from their supervisors and peers (Ng & Feldman, 2012). Third, empirical evidence in early studies have also supported that employees themselves could be an effective source in assessing their own creativity (e.g., Gilson et al, 2012;Janssen, 2000;Shalley, Gilson, & Blum, 2009). For example, Janssen (2000) found that self-rated employee creativity is significantly correlated to supervisorrated employee creativity.…”
Section: Measures Perceived Radical Creativity and Incremental Creatimentioning
confidence: 99%
See 1 more Smart Citation
“…Also, employees' perceptions of creativity could more accurately reflect creative habits as some employees may shield such behavior from their supervisors and peers (Ng & Feldman, 2012). Third, empirical evidence in early studies have also supported that employees themselves could be an effective source in assessing their own creativity (e.g., Gilson et al, 2012;Janssen, 2000;Shalley, Gilson, & Blum, 2009). For example, Janssen (2000) found that self-rated employee creativity is significantly correlated to supervisorrated employee creativity.…”
Section: Measures Perceived Radical Creativity and Incremental Creatimentioning
confidence: 99%
“…Since radical creativity and incremental creativity are quite distinct from one another, these two types of creativity may be developed through different processes and mechanisms. A few recent studies have identified several antecedents to radical and incremental creativity (Gilson, Lim, D'Innocenzo, & Moye, ; Gilson & Madjar, ; Madjar et al., ). These studies have found that various contextual factors such as creative co‐workers, resources (Madjar et al., ), and supportive supervision (Gilson et al., ) could affect these two types of creativity.…”
Section: Theories and Hypothesesmentioning
confidence: 99%
“…Some researchers have suggested that a deep level of involvement and absorption in an activity is required to generate breakthrough and novel ideas (Gilson, Lim, D'Innocenzo, & Moye, ). Therefore, it is probable that intrinsic rewards might trigger creativity that is high on novelty and originality because of the high level of involvement and absorption that these rewards create.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…Hence, encouraging and achieving a specific type of creativity desired at the given organizational and task conditions are crucial for managers (Alexander & van Knippenberg, ; Byron & Khazanchi, ). Despite this theoretical and practical significance, empirical studies that identify drivers and boundary conditions of different creativity types remain scarce (Gilson, Lim, D'Innocenzo, & Moye, ). The present study fills these research gaps by identifying and empirically investigating distinct motivational underpinnings and dispositional contingencies involving the radical and incremental creativity of employees.…”
Section: Introductionmentioning
confidence: 99%